PENGARUH PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) BERBANTUAN LEMBAR TUGAS PROYEK TERHADAP KOMPETENSI FISIKA SISWA KELAS X SMA NEGERI 3 PADANG - Azizah Fadhila; Yurnetti Yurnetti; Hidayati Hidayati (Universitas Negeri Padang, 2016)
Project Based Learning Model (PjBL) is one of teaching and learning model that is supported by 2013 curriculum. This model consists of systematic project procedures that can help students to find out the concept and understand how to work scientifically. It also can guide the students to think creative, active, independence and critically. When the students are active, creative and independence, it means they can dominate learning activities (students’ center). So this model is suitable to apply for the students. This research aims to find out “The effect of using Project Based Learning Model (PjBL) toward Physic Competence on first year student’s at Senior High School 3 Padang”. The types of this research was quasi-experimental research with randomize control group only design. The sample was taken by using purposive sampling. There were two classes: X MIA 4 as control class and X MIA 7 as experimental class. The data consisted of students’ attitude, knowledge and skill competencies. In collecting the data, the writer used written test for knowledge competence, observation for attitude competence and likert scale for skill competence. The data was analyzed by using test “t” formula for all competencies. The students’ score was compared with t-table at significance level of 5% which considered with degree of freedom (df). Based on data analysis, the writer found that there is significant effect of using project based learning (PjBL) toward physic competence on first year student’s at Senior High School 3 Padang in both competencies knowledge and skill but for attitude competence is rejected . So it can be concluded that; first, there is not significant effect of using project based learning (PjBL) toward students’ attitude competence on first year student’s at Senior High School 3 Padang; second, there is significant effect of using project based learning (PjBL) toward students’ knowledge competence on first year student’s at Senior High School 3 Padang; third, there is significant effect of using project based learning (PjBL) toward students’ skill competence on first year student’s at Senior High School 3 Padang